GUT MICROBIOTA AND HYGIENE THEORY OF ATOPY - A. V. Shestopalov; M. A. Shestopalova; E. V. Dudnikova; T. S. Kolmakova; V. A. Chistyakov (Медицинский вестник Юга России, 2013)
The indigenous gut microbiota plays a key role in maintaining homeostasis in gastrointestinal tract. The review is devoted to factors influencing gut microbiota composition, involvement of microbiota in formation of systemic and mucosal immunity, the role of disturbances of microbial community in development of allergic disease.